First in Human Phase I Trial of Dual Vector (HSV1-TK, Flt3L) Immunotherapy For The Treatment of Newly Diagnosed High-Grade Glioma: Initial Results. (1st September 2019) - Orringer, Daniel A; Sagher, Oren; Heth, Jason; Hervey-Jumper, Shawn L; Mammoser, Aaron; Junck, Larry; Leung, Denise; Umemura, Yoshie; Lawrence, Theodore; Kim, Michelle; Wahl, Dan; McKeever, Paul; et al.
Abstract: INTRODUCTION: An inadequate immune response is increasingly recognized as a central element in the pathogenesis of high-grade glioma. Based on our prior work, we hypothesized that dendritic cell dysfunction plays a key role in poor anti-brain tumor immunity. To stimulate a robust immune response against high-grade glioma, we developed a strategy to recruit dendritic cells to the brain and induce tumor cytotoxicity. We chose Flt3L to attract dendritic cells to the brain and HSV1-TK (plus valacyclovir) to kill tumor cells and make antigens available to dendritic cells. Studies in animal models of glioma reveal that Flt3L and HSV1-TK combination therapy results in infiltration of gliomas by dendritic cells, generation of immune cytotoxicity and memory, and the recognition of tumor neoantigens by immune cells. METHODS: Based on compelling preclinical data, we executed a first-in-human phase I dose escalation trial of HSV1-TK or Flt3L dual adenoviral therapy for the treatment of newly diagnosed malignant gliomas. Vectors were injected into the tumor cavity following resection. The trial consisted of a dose escalation of both vectors, starting at 1 × 10 ∧ 9 iu and increasing to 1 × 10 ∧ 11 iu through a total of 6 combinations administered to 6 cohorts of 3 patients each. Two cycles of 14 d each of valacyclovir were administered to activate HSV1-TK cytotoxicity on postoperative days 1 and 56. All patients received Stupp protocol chemoradiation. RESULTS: The experimental treatment was well tolerated, and at this time the MTD has not been reached. Additionally, preliminary analysis suggests that the dual-vector therapy provides a potent survival advantage when evaluated against contemporary and historical controls. Updated progression free survival and overall survival, AEs, and SAEs will be communicated at the time of presentation. CONCLUSION: Flt3L/HSV1-TK dual vector immunotherapy is well tolerated and may prolong survival in high-grade glioma patients. Further evaluation in a larger-scale, multi-center trial is justified.